1999
DOI: 10.1071/wr98059
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and density estimates for urban foxes (Vulpes vulpes) in Melbourne: implications for rabies control

Abstract: The distribution and density of red fox populations was investigated in metropolitan Melbourne from 1990 to 1993. Distribution data were collected from sightings reported by members of the public, from spotlight and active den surveys, and from trapping and road kills. Archival data suggested that resident populations of foxes have been present within the inner metropolitan area since the early 1940s. Contemporary fox populations were found to be extensively distributed throughout the urban area, with few 1-km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 18 publications
1
56
0
Order By: Relevance
“…Foxes, like most territorial animals, mark their territories and contact their neighbours regularly (White and Harris, 1994;Goszczynski, 2002). Studies have shown that contacts among territorial neighbours increase for rabid foxes and that fox group size can increase with density (Andral et al, 1982;Harris and Smith, 1987;Macdonald et al, 1999;Marks and Bloomfield, 1999;Baker et al, 2000). This evidence suggests that a mix of both linear density-dependent and densityindependent transmission functions is needed to model rabies transmission in these situations.…”
Section: Recent Stochastic Mixed Transmission Modelsmentioning
confidence: 99%
“…Foxes, like most territorial animals, mark their territories and contact their neighbours regularly (White and Harris, 1994;Goszczynski, 2002). Studies have shown that contacts among territorial neighbours increase for rabid foxes and that fox group size can increase with density (Andral et al, 1982;Harris and Smith, 1987;Macdonald et al, 1999;Marks and Bloomfield, 1999;Baker et al, 2000). This evidence suggests that a mix of both linear density-dependent and densityindependent transmission functions is needed to model rabies transmission in these situations.…”
Section: Recent Stochastic Mixed Transmission Modelsmentioning
confidence: 99%
“…Sargeant et al (1975) carried out an aerial den survey and located 84% of the family groups of foxes in their study area. Marks and Bloomfield (1999) estimated the density of fox groups using a combination of intensive ground searches and a media campaign asking residents to report dens. The status of the dens as breeding sites was established by detailed examination for signs of cub presence, and observation by spotlight (see below) was used to estimate mean litter size on a subsample.…”
Section: Counting Visible Structuresmentioning
confidence: 99%
“…The red fox was successfully introduced to Australia in the 1870s (Rolls 1969) and was first sighted in the inner metropolitan area of Melbourne during the late 1930s (Marks and Bloomfield 1999a), being common at a number of sites by the mid-1970s (Seebeck 1977). Foxes are currently present in every inner suburb of Melbourne and are known to inhabit the metropolitan areas of Perth, Adelaide and Brisbane (Marks and Bloomfield 1999a), Canberra (Jenkins and Craig 1992), and some outer (Mulley and Star 1983) and inner suburbs of Sydney (Chris Dickman, personal communication).…”
Section: Introductionmentioning
confidence: 99%